2013
DOI: 10.1007/s40620-013-0003-6
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid is the major determinant of absorbance in spent dialysate allowing spectrophotometric evaluation of dialysis dose

Abstract: UV absorbance is determined mostly by uric acid. Absorbance measurements seem suitable as a method for monitoring dialysis efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…3 ). This has been confirmed also by earlier studies [11,12] . Moreover, HPLC studies have demonstrated that UA is an UV-absorbing solute in the studied wavelength range, and therefore influences the UV-signal substantially [13] .…”
Section: Discussionsupporting
confidence: 90%
“…3 ). This has been confirmed also by earlier studies [11,12] . Moreover, HPLC studies have demonstrated that UA is an UV-absorbing solute in the studied wavelength range, and therefore influences the UV-signal substantially [13] .…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the contribution of β2M to the absorbance was relatively less and its contribution to fluorescence was absolutely negligible. Thus, the absorbance at 280 nm is mainly due to other substances, namely, uric acid [5] . In fact, significant UV absorption and fluorescence emission signals were also measured treatments with the LF membrane, which do not allow any β2M transfer, as demonstrated by the absence 112 of β2M in spent dialysate.…”
Section: The Contribution Of β2-microglobulin To Uv Absorption and Flmentioning
confidence: 99%
“…An emission peak at 340 nm was observed in the fluorescence spectrum of β2M in the range 230-510 nm Toxins are removed from plasma and filtered into the spent dialysate or ultra-filtrate, via diffusion and convection, or trapped inside the membrane by adsorption. It has been already demonstrated that the analysis of spent dialysate by spectrophotometry allows the monitoring of dialysis removal of small molecules and the noninvasive assessment of dialysis efficiency and Kt/V [1][2][3][4][5] . The removal of β2-microglobulin (β2M, MW 11.8 kDa) from plasma is considered an effective marker of the dialyzer clearance for 'middle molecules' and proteins with molecular weight ranging 10-30 kDa [6] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…; Donadio et al . ), although the absorption depends on several substances with different distribution volumes and kinetics. A straight regression line can of course be drawn through almost any group of points resulting that the measurements are forced erroneously into a single pool model.…”
Section: Introductionmentioning
confidence: 99%